Biochar production from sugarcane biomass using slow pyrolysis: Characterization of the solid fraction - de Almeida, Sâmilla G.C. [UNESP]; Tarelho, Luís A.C.; Hauschild, Tailane; Costa, Maria Angélica Martins [UNESP]; Dussán, Kelly J. [UNESP] (Elsevier, 2022)
Understanding how the type of biomass t and parameters of the pyrolysis process influence the characteristics of the biochar obtained, including its calorific value and potential as solid fuel, is important in generating alternative energy sources. In this context, this study assesses biochar production by pyrolysis of parent biomass (B), straw (S), and treated biomass (T, processed with H2SO4 0.5% (w/v) at 140 °C for 15 min). The pyrolysis process of B at 450, 550, and 650 °C, S at 450 °C, and T at 450°C was conducted in a bench-scale fixed-bed reactor at a heating rate of 10°C/min. The higher yield of biochar (50.3 wt% db) and bio-oil (26.0 wt% db) for the B was observed at 450°C. Furthermore, the biochar yields for S and T at 450 °C were 36.8 and 31.3 (wt% db), respectively. The biochar produced from B, S, and T at 450 °C shows a higher heating value of 27.9, 25.4, and 27.0 MJ/kg db, respectively. The elemental analysis of the biochar produced from the different feedstocks showed a higher C (64.91–80.93%) and a lower O content (22.58–30.5%) than the parent biomass, indicating that the biochar has good stability and potential as an energy carrier. The approach followed in this work was to contribute to a more in-depth understanding of the valorization of subproducts of the sugarcane industry through pyrolysis to produce biochar that can be used as an energy vector or material for different environmental applications, contributing to the goals of a circular bioeconomy.
Keywords: Biochar; Biofuels; Biomass; Pyrolysis; Thermochemical process